â€œBig Pushâ€ Hypothesis and Development Paradigm in Nigeria - Mahmud, Umar Elems; Aliegba, Becky; Yakubu, Shehu Ibrahim (NIU Journal of Social Sciences, 2020)
The needed theoretical impetus for leap-frogging the economies of poor countries, Nigeria inclusive, over underdevelopment was provided by Professor Paul N. Rodestein-Rodanâ€™s â€œBig-Pushâ€ Theory in 1943. The cardinal thesis of the Theory is that, in contradistinction to â€œbit-by-bitâ€ approach, massive capital investment in social and economic infrastructure is required to give an underdeveloped economy a â€œbig-pushâ€ out of the doldrums. Evidence from the legion of theoretical literature and occasional commentaries supports the ineluctability of the critical and frontline role of Government in achieving the Herculean task. Unfortunately however, Governmentâ€™s attitude in Nigeria has smacked of incuriousity and exacerbated the situation, through derisory budgetary appropriation for capital expenditure. The key objective of this study therefore is to examine the nature, causes and implications of the observed Governmentâ€™s â€œanti-growth attitudeâ€. In the theoretical framework comprising of an admixture of â€œBig-Pushâ€ theory and Structural-Functionalism, content analysis and primary survey provide the research design; while Chi-square statistical tool was employed in examining the discrepancy between the observed and expected capital appropriations by the Federal Government of Nigeria during the study period, 2006-2019. The findings of the study largely support the priori expectation of a significant discrepancy. Accordingly, it is recommended that Government should re-prioritise huge capital investment, by appropriating a minimum of 60 per cent of annual total budgetary expenditure for capital or investment, an improvement over the 40 per cent benchmark prescribed by Rodestein-Rodan in the Big-Push Theory, adjusting for â€œtime effectâ€.     Keywords: Big-Push, Underdeveloped Economy, Capital Expenditure, Recurrent Expenditure, Budgetary Allocation, Discrepancy.